Separator for power storage devices and power storage device
Patent Information
- Application Number
- JP2023131308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0012】 本発明によれば、高突刺強度と低透気度とを兼ね備え、かつ薄膜化の可能な蓄電デバイス用セパレータを提供することができる。
Smart Images

Figure 2025025994000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a separator for an electricity storage device, etc. [Background technology]
[0002] Microporous membranes, particularly polyolefin-based microporous membranes, are used in many technical fields such as microfiltration membranes, battery separators, capacitor separators, fuel cell materials, etc., and are particularly used as separators for power storage devices such as lithium secondary batteries and lithium ion secondary batteries. Lithium ion batteries are used in various applications such as small electronic devices such as mobile phones and notebook personal computers, as well as electric vehicles including hybrid automobiles and plug-in hybrid automobiles.
[0003] In recent years, there has been a demand for lithium ion batteries having high energy capacity, high energy density, and high output characteristics. Accordingly, there is an increasing demand for thin separators that are excellent in battery performance, reliability, and safety.
[0004] For example, US Patent No. 5,999,943 describes multilayer microporous thin films or membranes that can improve properties including dielectric breakdown and strength. A preferred multilayer microporous membrane includes a microlayer and one or more stacked barriers.
[0005] Patent Document 2 describes a separator for an electricity storage device that has high strength and can be made thin, and discloses a microporous membrane that contains polyolefin as a main component and has a melt tension of 30 mN or less when measured at a temperature of 230°C, and a melt flow rate (MFR) of 0.9 g / 10 min or less when measured under a load of 2.16 kg at a temperature of 230°C.
[0006] Patent Document 3 describes a separator for an electricity storage device that is excellent in terms of product safety, and discloses a microporous membrane that contains a polypropylene resin and a thermoplastic elastomer and has a specific MFR and morphology.
[0007] Patent Document 4 describes a separator for lithium-ion lithium batteries that has excellent air permeability and shutdown properties, and discloses a porous film having a mixed resin layer containing a polypropylene resin, a polyethylene resin, and a thermoplastic resin whose crystal melting peak temperature or glass transition temperature is equal to or lower than the crystal melting peak temperature of the polyethylene resin, and having β activity. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2018 / 089748 [Patent Document 2] International Publication No. 2020 / 196120 [Patent Document 3] International Publication No. 2019 / 103947 [Patent Document 4] JP 2010-111832 A Summary of the Invention [Problem to be solved by the invention]
[0009] In the methods described in Patent Documents 1 to 4, a thin film, high strength, excellent air permeability, and the like are achieved by using specific membrane properties or resin mixtures. However, a separator that is thin and has high strength while also having low air permeability is required for an electricity storage device, and from this perspective, there is room for further improvement.
[0010] Therefore, an object of the present invention is to provide a separator for an electricity storage device that has both high puncture strength and low air permeability and can be made thin. [Means for solving the problem]
[0011] As a result of extensive investigations, the inventors have found that the above problems can be solved by using a separator substrate that contains a polyolefin containing specific amounts of polypropylene and polyethylene, and a specific amount of a thermoplastic elastomer in the same layer, and has a microporous membrane layer with a specific melt flow rate (MFR), and have completed the present invention. That is, the present invention is as follows. (1) A separator for an electricity storage device, comprising a microporous layer (A) containing a polyolefin as a main component and a thermoplastic elastomer as a separator substrate, The microporous layer (A) contains polypropylene and polyethylene as the polyolefin, The microporous layer (A) contains, based on the total mass of the microporous layer (A), 80.0% by mass or more and 99.5% by mass or less of the polyolefin and 0.5% by mass or more and 20.0% by mass or less of the thermoplastic elastomer, and contains, based on the total mass of the polyolefin excluding the thermoplastic elastomer, 80.0% by mass or more and 99.5% by mass or less of the polypropylene and 0.5% by mass or more and 20.0% by mass or less of the polyethylene, The microporous layer (A) has a melt flow rate (MFR) of 0.90 g / 10 min or less when measured under a load of 2.16 kg at a temperature of 230° C. (2) Melt tension Mt of the microporous layer (A) at 240°C A 2. The separator for an electricity storage device according to item 1, wherein the compressive strength is 10 mN or more and 35 mN or less. (3) The separator for an electricity storage device according to item 1 or 2, wherein the microporous layer (A) has a weight average molecular weight (Mw) of 250,000 or more and 1,500,000 or less. (4) The separator for an electricity storage device according to item 3, wherein the molecular weight distribution (Mw / Mn) of the microporous layer (A), which is the weight average molecular weight (Mw) divided by the number average molecular weight (Mn), is 3 or more and 30 or less. (5) In the microporous layer (A), in a differential scanning calorimetry (DSC) curve during a temperature rise, there is an endothermic peak A having a peak value in the range of 100°C to 145°C and an endothermic peak B having a peak value in the range of 155°C to 175°C, and the area S of the endothermic peak A is A and the area S of the endothermic peak B B Ratio to S B / S A 5. The separator for an electricity storage device according to any one of items 1 to 4, wherein the value of Mn is 2 or more and 200 or less. (6) The separator for an electricity storage device according to any one of items 1 to 5, wherein the microporous layer (A) has a melt flow rate (MFR) of 0.30 g / 10 min or more when measured under a load of 2.16 kg at a temperature of 230° C. (7) The separator for an electricity storage device according to any one of items 1 to 6, wherein the microporous layer (A) contains 90.0% by mass or more of the polyolefin and 10.0% by mass or less of the thermoplastic elastomer, based on the total mass of the microporous layer (A), and contains 90.0% by mass or more of the polypropylene and 10.0% by mass or less of the polyethylene, based on the total mass of the polyolefin excluding the thermoplastic elastomer. (8) The separator for an electricity storage device according to any one of items 1 to 7, wherein the polypropylene has a weight average molecular weight (Mw) of 300,000 or more and 1,300,000 or less. (9) 13 9. The separator for an electricity storage device according to any one of items 1 to 8, wherein the polypropylene has a pentad fraction of 94.0% or more as measured by C-NMR (nuclear magnetic resonance). (10) The separator for an electricity storage device according to any one of items 1 to 9, wherein the polyethylene has a weight average molecular weight (Mw) of 100,000 or more and 1,800,000 or less. (11) The separator for an electricity storage device according to any one of items 1 to 10, wherein the thermoplastic elastomer contains, as a repeating unit, at least one selected from the group consisting of ethylene, propylene, and 1-butene. (12) The separator for an electricity storage device according to any one of items 1 to 11, wherein the separator substrate is a single layer of the microporous layer (A) or a multilayer including the microporous layer (A), and the porosity of the separator substrate is 40% or more and 60% or less. (13) The separator for an electricity storage device according to any one of items 1 to 12, wherein the separator substrate has a thickness of 3 μm or more and 20 μm or less. (14) The separator for an electricity storage device according to any one of items 1 to 13, wherein the area average pore diameter calculated by analysis of a scanning electron microscope (SEM) image of a MD-ND cross section of the microporous layer (A) is 50 nm or more and 500 nm or less. (15) The separator for an electricity storage device according to any one of items 1 to 14, wherein the separator substrate has a TD heat shrinkage of 5% or less at a temperature of 105° C. for 1 hour. (16) The separator for an electricity storage device according to any one of items 1 to 15, wherein the separator substrate has an MD heat shrinkage rate of 20% or less at a temperature of 105° C. for 1 hour. (17) The separator for an electricity storage device according to any one of items 1 to 16, wherein the separator substrate has an MD tensile elongation of 20% or more and 60% or less. (18) The separator substrate has a melt tension Mt A and different melt tension Mt B 18. The separator for an electricity storage device according to any one of items 1 to 17, comprising a microporous layer (B) which is (19) An electricity storage device comprising: a positive electrode; a negative electrode; and the separator for an electricity storage device according to any one of items 1 to 18, disposed between the positive electrode and the negative electrode. (20) The power storage device according to item 19, wherein the positive electrode contains lithium iron phosphate as a positive electrode active material. (21) The steps of: An annealing step of annealing a resin sheet containing polypropylene, polyethylene, and a thermoplastic elastomer at a temperature of 135°C or more and 160°C or less; and A heat treatment step of stretching the annealed resin sheet in MD at a temperature of 130°C or more and 155°C or less; 19. A method for producing a separator for an electricity storage device according to any one of items 1 to 18, comprising: Effect of the Invention
[0012] According to the present invention, it is possible to provide a separator for an electricity storage device that has both high puncture strength and low air permeability and can be made thin. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram illustrating the relationship between the polymer matrix, connecting domains, fibrils, and pores in a cross section of a microporous layer (A) produced by uniaxial stretching in the film formation direction (MD) according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] <Separator for power storage device> The separator for an electric storage device of the present disclosure has a microporous layer (A) containing polyolefin as a main component and containing a thermoplastic elastomer as a separator substrate. The separator substrate may optionally contain a microporous layer (B) containing polyolefin as a main component in addition to the microporous layer (A). The separator substrate may further have a coating layer (also called a "surface layer", a "coating layer", etc., hereinafter simply referred to as a "coating layer") on the microporous layer (A) and / or the microporous layer (B). In the present disclosure, the "microporous layer" refers to each microporous layer constituting the substrate of the separator, the "separator substrate" refers to the substrate of the separator excluding any coating layer, and the "separator" refers to the entire separator including any coating layer.
[0015] <Microporous layer (A)> The separator for an electric storage device of the present disclosure has a microporous layer (A). The separator for an electric storage device may have only one microporous layer (A) or two or more layers. The microporous layer (A) is mainly composed of polyolefin and contains a thermoplastic elastomer, and contains polypropylene and polyethylene as the polyolefin in the same layer. In the present disclosure, the microporous layer (A) contains 80.0% by mass or more and 99.5% by mass or less of polyolefin and 0.5% by mass or more and 20.0% by mass or less of thermoplastic elastomer based on the total mass of the microporous layer (A), and also contains 80.0% by mass or more and 99.5% by mass or less of polypropylene and 0.5% by mass or more and 20.0% by mass or less of polyethylene based on the total mass of polyolefin excluding the thermoplastic elastomer.
[0016] As described above, the microporous layer (A) of the present disclosure contains polypropylene, polyethylene, and a thermoplastic elastomer as constituent materials. The morphology of the microporous layer (A) of the present disclosure is not limited, but for example, the morphology when produced by uniaxial stretching in the film formation direction (MD) is as shown in FIG. 1. It is preferable that a plurality of fibrils (3) extend along the MD of the microporous layer (A) between a plurality of polymer matrices (1), that linking domains (2) are oriented in parallel to the MD of the microporous layer (A) inside or on the surface of the polymer matrix (1) and / or between the plurality of polymer matrices (1), and that the portion other than the polymer matrix (1), the fibrils (3), and the linking domains (2) are voids (4). It is preferred that the polymer matrix contains at least polypropylene, and when produced by uniaxial stretching, the structure is one in which lamellar crystals are arranged, the fibrils contain at least polypropylene, and when produced by uniaxial stretching, the fibrils are formed by stretching the polymer chains of the polymer matrix during pore opening by stretching, and the connecting domains contain polyethylene and / or a thermoplastic elastomer.
[0017] Without being limited by theory, it is important that the microporous layer (A) of the present disclosure has a connecting domain formed, and it is presumed that by reinforcing the polymer matrix without excessively crushing the pores, it is possible to form a microporous layer (A) that has both low air permeability and high pin puncture strength. The breakage mode of the pin puncture strength in the microporous layer (A) includes cracking of the polymer matrix. It is considered that the presence of a connecting domain inside or on the surface of the polymer matrix and / or between multiple polymer matrices makes it possible to relieve the stress applied to the polymer matrix at the time of breakage, and high pin puncture strength can be expressed. In the microporous layer (A) of the present disclosure, a small amount of polyethylene is contained or added to polypropylene, but since polypropylene and polyethylene are generally immiscible, a part or all of the polyethylene that is not mixed with the polymer matrix containing the main component polypropylene forms a domain different from the polymer matrix. In addition, it is presumed that the thermoplastic elastomer improves the dispersibility of polypropylene and polyethylene, or plays a role in connecting polypropylene and polyethylene to strengthen the connection of the domains, thereby promoting the above effect as a connecting domain. From the viewpoint of achieving both low air permeability and high pin puncture strength of the thin film, it is preferable that the connecting domain containing polyethylene extends uninterruptedly along the MD as shown in FIG.
[0018] The lower limit of the polyolefin content in the microporous layer (A) is preferably 85.0% by mass or more, more preferably 90.0% by mass or more, even more preferably 92.5% by mass or more, and even more preferably 95.0% by mass or more, based on the total mass of the microporous layer (A), from the viewpoint of pore opening, etc. The upper limit of the polyolefin content in the microporous layer (A) is preferably 99.0% by mass or less, more preferably 98.5% by mass or less, even more preferably 98.0% by mass or less, and even more preferably 97.5% by mass or less, based on the total mass of the microporous layer (A), from the viewpoint of obtaining good battery performance.
[0019] The lower limit of the content of the thermoplastic elastomer in the microporous layer (A) is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, and even more preferably 3.0% by mass or more, based on the total mass of the microporous layer (A), from the viewpoints of film-forming property, thinning, low air permeability, and high pin puncture strength. The upper limit of the content of the thermoplastic elastomer in the microporous layer (A) is preferably 15.0% by mass or less, more preferably 10.0% by mass or less, more preferably 7.5% by mass or less, and even more preferably 5.0% by mass or less, based on the total mass of the microporous layer (A), from the viewpoints of maintaining pore opening.
[0020] The microporous layer (A) contains 80.0% by mass or more and 99.5% by mass or less of polypropylene based on the total mass of polyolefin excluding thermoplastic elastomer. This allows good battery performance to be maintained even after storage at high temperatures (e.g., 130°C). The lower limit of the content of polypropylene in polyolefin excluding thermoplastic elastomer is preferably 85.0% by mass or more, more preferably 90.0% by mass or more, even more preferably 92.5% by mass or more, and even more preferably 95.0% by mass or more, based on the total mass of polyolefin excluding thermoplastic elastomer, from the viewpoint of maintaining good battery performance even after storage at high temperatures (e.g., 130°C). The upper limit of the content of polypropylene in polyolefin excluding thermoplastic elastomer is preferably 99.0% by mass or less, more preferably 98.5% by mass or less, even more preferably 98.0% by mass or less, and even more preferably 97.5% by mass or less, based on the total mass of polyolefin excluding thermoplastic elastomer, from the viewpoint of maintaining good pin puncture strength and air permeability.
[0021] The microporous layer (A) contains polypropylene and polyethylene in the same layer, and contains 0.5% by mass or more and 20.0% by mass or less of polyethylene based on the total mass of polyolefins excluding thermoplastic elastomers. As a result, as described above, a part or all of the polyethylene that is not mixed with the polymer matrix containing polypropylene forms a domain different from the polymer matrix, making it possible to form a microporous layer (A) that has both low air permeability and high pin puncture strength. The lower limit of the content of polyethylene in the polyolefin excluding thermoplastic elastomers is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, and even more preferably 3.0% by mass or more, based on the total mass of polyolefins excluding thermoplastic elastomers, from the viewpoint of achieving both high pin puncture strength and low air permeability. The upper limit of the content of polyethylene in the polyolefin excluding thermoplastic elastomers is preferably 15.0% by mass or less, more preferably 12.5% by mass or less, more preferably 10.0% by mass or less, and even more preferably 7.5% by mass or less, based on the total mass of polyolefins excluding thermoplastic elastomers, from the viewpoint of maintaining openness.
[0022] <Material for the microporous layer (A)> The microporous layer (A) contains polyolefin as a main component, and polypropylene and polyethylene in the same layer. By using polyolefin as a main component of the microporous layer (A), the substrate or separator has good pore opening and good battery performance can be obtained. The polypropylene of the microporous layer (A) may be the same material as the polypropylene of the microporous layer (B) described later, or may be a polypropylene having a different chemical structure, more specifically, a polypropylene having at least one different monomer composition, stereoregularity, molecular weight, and crystal structure. The stereoregularity of the polypropylene is not limited, and examples thereof include atactic, isotactic, or syndiotactic homopolymers. The polypropylene according to the present disclosure is preferably a highly crystalline isotactic or syndiotactic homopolymer.
[0023] The polypropylene of the microporous layer (A) is preferably a homopolymer, and may be a copolymer, such as a block polymer, in which a small amount of comonomer other than propylene, such as an α-olefin comonomer, is copolymerized. The amount of propylene structure contained as a repeating unit in the polypropylene is not limited, but may be, for example, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 99 mol% or more. The amount of repeating units derived from comonomers other than the propylene structure contained in the polypropylene is not limited, but may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less. The polypropylene may be used alone or in a mixture of two or more kinds.
[0024] The weight average molecular weight (Mw) of the polypropylene of the microporous layer (A) is preferably 300,000 or more from the viewpoint of high pin puncture strength of the microporous layer, and is preferably 1,300,000 or less from the viewpoint of ensuring good film-forming properties, productivity, thinning and low air permeability. The Mw of the polypropylene is more preferably 500,000 or more and 1,200,000 or less, even more preferably 650,000 or more and 1,100,000 or less, still more preferably 750,000 or more and 1,000,000 or less, and particularly preferably 800,000 or more and 1,000,000 or less.
[0025] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the polypropylene of the microporous layer (A) by the number average molecular weight (Mn) is preferably 20 or less, more preferably 18 or less, 16 or less, 14 or less, or 12 or less. By making the Mw / Mn of the polypropylene 20 or less, there is a tendency that good film-forming properties, productivity, and thinning can be ensured. In addition, the lower limit of the Mw / Mn of the polypropylene is preferably 3 or more, more preferably 4 or more, 4.5 or more, or 5.0 or more. By making the Mw / Mn of the polypropylene 3 or more, appropriate molecular entanglement is maintained, and good film-forming stability is obtained. The weight average molecular weight, number average molecular weight, and Mw / Mn of the polypropylene of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement.
[0026] The density of the polypropylene of the microporous layer (A) is preferably 0.85 g / cm 3 For example, 0.88 g / cm 3 More than 0.89g / cm 3 or more than 0.90g / cm 3 The density of polypropylene is preferably 1.1 g / cm or more. 3 For example, 1.0 g / cm 3 Below, 0.98g / cm 3 Below, 0.97g / cm 3 Below, 0.96g / cm 3 Below, 0.95g / cm 3 Below, 0.94g / cm 3 Below, 0.93g / cm 3 or less than 0.92 g / cm 3 The density of polypropylene is related to the crystallinity of polypropylene, and the density of polypropylene may be less than 0.85 g / cm 3 By setting the above amount, the productivity of the microporous layer is improved, which is particularly advantageous in the dry method.
[0027] The lower limit of the pentad fraction of the polypropylene in the microporous layer (A) is preferably 94.0% or more, for example, 95.0% or more, 96.0% or more, 96.5% or more, 97.0% or more, 97.5% or more, 98.0% or more, 98.5% or more, or 99.0% or more, from the viewpoint of obtaining a microporous layer with low air permeability. The upper limit of the pentad fraction of the polypropylene is not limited, but may be 99.9% or less, 99.8% or less, or 99.5% or less. The pentad fraction of the polypropylene is 13 Measured by C-NMR (nuclear magnetic resonance).
[0028] A pentad fraction of 94.0% or more of the polypropylene in the microporous layer (A) indicates that the polypropylene has high crystallinity. In a separator obtained by the stretching perforation method, particularly the dry method, the amorphous parts between the crystalline parts are stretched to form pores, so if the polypropylene has high crystallinity, the pores become good and the air permeability can be kept low, enabling the battery to have high input and output.
[0029] Examples of polyethylene for the microporous layer (A) include ultra-high molecular weight polyethylene, high density polyethylene, low density polyethylene, and linear low density polyethylene. These may be used alone or in combination of two or more. In addition, polyethylene with a narrow molecular weight distribution using a metallocene catalyst, high density polyethylene, or polyethylene by multi-stage polymerization may be used. Among the above, high density polyethylene is preferred from the viewpoints of film-forming properties and high pin puncture strength.
[0030] The polyethylene of the microporous layer (A) is preferably a homopolymer, and may be a copolymer, such as a block polymer, in which a small amount of a comonomer other than ethylene, such as an α-olefin comonomer, is copolymerized. The amount of ethylene structure contained as a repeating unit in the polyethylene is not limited, but may be, for example, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 99 mol% or more. The amount of repeating units derived from comonomers other than ethylene structure contained in the polyethylene is not limited, but may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less. The polyethylene may be used alone or in combination of two or more kinds.
[0031] The weight average molecular weight (Mw) of the polyethylene of the microporous layer (A) is preferably 100,000 or more from the viewpoint of high pin puncture strength due to the formation of connected domains in the microporous layer, and is preferably 1,800,000 or less from the viewpoint of ensuring good film-forming properties, thinning, and productivity. The Mw of the polyethylene is more preferably 150,000 or more and 1,500,000 or less, even more preferably 200,000 or more and 1,200,000 or less, still more preferably 250,000 or more and 900,000 or less, and particularly preferably 300,000 or more and 600,000 or less.
[0032] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the polyethylene of the microporous layer (A) by the number average molecular weight (Mn) is preferably 24 or less, more preferably 22 or less, 20 or less, or 18 or less. By setting the Mw / Mn of the polyethylene to 24 or less, good film-forming properties, thinning, and productivity tend to be ensured. In addition, the lower limit of the Mw / Mn of the polyethylene is preferably 3 or more, more preferably 4 or more, 4.5 or more, or 5.0 or more. By setting the Mw / Mn of the polyethylene to 3 or more, appropriate molecular entanglement is maintained, and good film-forming stability is obtained. The weight average molecular weight, number average molecular weight, and Mw / Mn of the polyethylene of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement.
[0033] The density of the polyethylene of the microporous layer (A) is preferably 0.85 g / cm 3 For example, 0.88 g / cm 3 More than 0.89g / cm 3 or more than 0.90g / cm 3 The density of the polyethylene is preferably 1.1 g / cm or more. 3 For example, 1.0 g / cm 3 Below, 0.98g / cm 3 Below, 0.97g / cm 3 Below, 0.96g / cm 3 Below, 0.95g / cm 3 Below, 0.94g / cm 3 Below, 0.93g / cm 3 or less than 0.92 g / cm 3 The density of polyethylene is related to the crystallinity of the polyethylene, and the density of polyethylene may be less than 0.85 g / cm 3 By doing so, a microporous layer having high pin puncture strength can be obtained due to the formation of linked domains.
[0034] The microporous layer (A) is mainly composed of polyolefin, but may contain polyolefin other than polypropylene and polyethylene. Polyolefin is a polymer containing a monomer having a carbon-carbon double bond as a repeating unit. Monomers constituting polyolefin other than polypropylene and polyethylene are not limited, but include monomers having 4 to 10 carbon atoms and having a carbon-carbon double bond, such as 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Examples of polyolefin include homopolymers, copolymers, and multi-stage polymerization polymers.
[0035] The microporous layer (A) contains polyolefin as a main component and also contains a thermoplastic elastomer. Examples of the thermoplastic elastomer include a polyolefin different from the main component, a copolymer of polyolefin, and a copolymer of polystyrene and polyolefin. A polyolefin is a polymer containing a monomer having a carbon-carbon double bond as a repeating unit. Examples of monomers constituting polyolefin include, but are not limited to, monomers having 2 to 10 carbon atoms (C2 to C10) and having a carbon-carbon double bond, such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Examples of polyolefin include low-crystalline polypropylene having a low stereoregularity region. As the monomers constituting the polyolefin copolymer, one type may be used alone, or two or more types may be mixed and used. Examples of copolymers of polystyrene and polyolefin include styrene-(ethylene-propylene)-styrene copolymer (SEPS), styrene-(ethylene-butene)-styrene copolymer (SEBS), styrene-ethylene-styrene copolymer, styrene-(ethylene-butene)-olefin copolymer (SEBC), olefin-(ethylene-butene)-styrene copolymer (CEBS), etc., which may be hydrogenated polymers. These copolymers may be random copolymers or block copolymers, and are preferably block copolymers.
[0036] As the thermoplastic elastomer contained in the microporous layer (A) of the present disclosure, from the viewpoint of obtaining a microporous layer (A) that has both high pin puncture strength and low air permeability by improving the dispersibility of polypropylene and polyethylene or by linking polypropylene and polyethylene to strengthen the connection of domains, as described above, a copolymer containing one or more repeating units selected from the group consisting of ethylene, propylene, and 1-butene that is compatible with polypropylene and / or polyethylene is preferred. Among them, ethylene / propylene (C2C3) copolymer, ethylene / 1-hexene (C2C6) copolymer, ethylene / 1-octene (C2C8) copolymer, olefin-(ethylene-butene)-olefin copolymer (CEBC), olefin-(ethylene-butene)-styrene copolymer (CEBS) are more preferred, and ethylene / propylene (C2C3) copolymer, ethylene-terminated olefin-(ethylene-butene)-olefin copolymer (CEBC), and ethylene-terminated olefin-(ethylene-butene)-styrene copolymer (CEBS) are even more preferred. Here, the ethylene-butene structure is structurally similar to propylene, and therefore has high affinity with polypropylene. The thermoplastic elastomers can be used alone or in combination of two or more.
[0037] <Melt flow rate (MFR) of microporous layer (A)> The melt flow rate (MFR) of the microporous layer (A) of the present disclosure is 0.90 g / 10 min or less. From the viewpoint of obtaining a microporous layer (A) with higher pin puncture strength, the upper limit of the melt flow rate (MFR) of the microporous layer (A) (MFR of a single layer) is preferably 0.80 g / 10 min or less, more preferably 0.70 g / 10 min or less, even more preferably 0.65 g / 10 min or less, and even more preferably 0.60 g / 10 min or less. The lower limit of the MFR of the microporous layer (A) (single layer MFR) is not limited, but from the viewpoint of obtaining a microporous layer (A) with lower air permeability, film-forming property and thinner film, it may be, for example, 0.20 g / 10 min or more, 0.25 g / 10 min or more, 0.30 g / 10 min or more, 0.35 g / 10 min or more, 0.40 g / 10 min or more, or 0.45 g / 10 min or more. The MFR of the microporous layer (A) is measured under conditions of a load of 2.16 kg and a temperature of 230°C. The MFR of the microporous layer (A) being 0.90 g / 10 min or less means that the molecular weight of the polyolefin contained in the microporous layer (A) is significantly high. The high molecular weight of the polyolefin increases the number of tie molecules that bond crystalline substances together, and therefore tends to obtain a microporous layer (A) with high pin puncture strength. Furthermore, when the microporous layer (A) has an MFR of 0.20 g / 10 min or more, the melt tension of the microporous layer (A) does not become too high, and good film-forming properties, thin film thickness, and productivity can be ensured.
[0038] From the viewpoint of obtaining a microporous layer (A) having high puncture strength, low air permeability and a thin film, the MFR of the polypropylene of the microporous layer (A) is preferably 0.2 to 0.9 g / 10 min when measured under conditions of a load of 2.16 kg and a temperature of 230° C. From the viewpoint of obtaining a microporous layer (A) having higher puncture strength, the upper limit of the MFR of the polypropylene may be, for example, 0.8 g / 10 min or less, 0.7 g / 10 min or less, 0.65 g / 10 min or less, 0.6 g / 10 min or less, or 0.55 g / 10 min or less. The lower limit of the MFR of the polypropylene is not limited, but from the viewpoint of obtaining a microporous layer (A) with lower air permeability, film formability, and a thinner film, it may be, for example, 0.2 g / 10 min or more, 0.25 g / 10 min or more, 0.3 g / 10 min or more, 0.35 g / 10 min or more, 0.4 g / 10 min or more, or 0.45 g / 10 min or more.
[0039] From the viewpoint of obtaining a microporous layer (A) having high puncture strength, low air permeability and a thin film, the MFR of the polyethylene of the microporous layer (A) is preferably 0.005 to 10.0 g / 10 min when measured under conditions of a load of 2.16 kg and a temperature of 190°C. From the viewpoint of obtaining a microporous layer (A) having higher puncture strength and good film-formability stability, the upper limit of the MFR of the polyethylene may be, for example, 8.0 g / 10 min or less, 6.0 g / 10 min or less, 4.0 g / 10 min or less, 3.0 g / 10 min or less, 2.0 g / 10 min or less, 1.5 g / 10 min or less, 1.0 g / 10 min or less, 0.8 g / 10 min or less, 0.6 g / 10 min or less, 0.5 g / 10 min or less, 0.4 g / 10 min or less, 0.35 g / 10 min or less, 0.3 g / 10 min or less, 0.25 g / 10 min or less, 0.2 g / 10 min or less, 0.15 g / 10 min or less, 0.1 g / 10 min or less, or 0.05 g / 10 min or less. The lower limit of the MFR of the polyethylene is not limited, but from the viewpoint of obtaining a microporous layer (A) with lower air permeability, film formability, and a thinner film, it may be, for example, 0.008 g / 10 min or more, 0.01 g / 10 min or more, 0.012 g / 10 min or more, 0.015 g / 10 min or more, 0.018 g / 10 min or more, or 0.02 g / 10 min or more.
[0040] From the viewpoint of obtaining a microporous layer (A) having high pin puncture strength, low air permeability, a thin film, and good film-forming stability, the MFR of the thermoplastic elastomer of the microporous layer (A) is preferably 0.1 to 100.0 g / 10 min when measured under conditions of a load of 2.16 kg and a temperature of 230° C. The upper limit of the MFR of the thermoplastic elastomer may be, for example, 80.0 g / 10 min or less, 60.0 g / 10 min or less, 40.0 g / 10 min or less, 30.0 g / 10 min or less, 20.0 g / 10 min or less, 15.0 g / 10 min or less, 10.0 g / 10 min or less, 8.0 g / 10 min or less, 6.0 g / 10 min or less, or 5.0 g / 10 min or less, from the viewpoint of obtaining a microporous layer (A) that is uniformly kneaded with the polyolefin and has high pin puncture strength and good film-forming stability. The lower limit of the MFR of the thermoplastic elastomer is not limited, but from the viewpoint of obtaining a microporous layer (A) with lower air permeability, film formability, and a thinner film, it may be, for example, 0.5 g / 10 min or more, 1.0 g / 10 min or more, 1.5 g / 10 min or more, 2.0 g / 10 min or more, 2.5 g / 10 min or more, or 3.0 g / 10 min or more.
[0041] <Mw and Mw / Mn of the microporous layer (A)> The weight average molecular weight (Mw) of the microporous layer (A) is preferably 250,000 or more from the viewpoint of obtaining a microporous layer (A) with higher pin puncture strength, and is preferably 1,500,000 or less from the viewpoint of ensuring good film-forming properties, productivity, thinning and low air permeability. The Mw of the microporous layer (A) is more preferably 400,000 or more and 1,300,000 or less, even more preferably 500,000 or more and 1,200,000 or less, still more preferably 600,000 or more and 1,100,000 or less, and particularly preferably 700,000 or more and 1,000,000 or less.
[0042] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the microporous layer (A) by the number average molecular weight (Mn) is preferably 30 or less, more preferably 25 or less, 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, or 10 or less. By making the Mw / Mn of the microporous layer (A) 30 or less, good film-forming properties, productivity, and thinning tend to be ensured. In addition, the lower limit of the Mw / Mn of the microporous layer (A) is preferably 3 or more, more preferably 4 or more, 4.5 or more, or 5.0 or more. By making the Mw / Mn of the microporous layer (A) 3 or more, appropriate molecular entanglement is maintained, and good film-forming stability is obtained. The weight average molecular weight, number average molecular weight, and Mw / Mn of the microporous layer (A) of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement. Furthermore, since the microporous layer (A) of the present disclosure contains polyolefins including polypropylene and polyethylene as main components and also contains a thermoplastic elastomer, the above-mentioned Mw and Mw / Mn of the microporous layer (A) are values that reflect the influence of the combination of these constituent materials.
[0043] <Melt tension of microporous layer (A)> Melt tension Mt of the microporous layer (A) at 240°C A (Single layer Mt A The upper limit of the melt tension Mt of the microporous layer (A) is preferably 35 mN or less, more preferably 32 mN or less, even more preferably 30 mN or less, still more preferably 28 mN or less, and particularly preferably 26 mN or less, from the viewpoints of obtaining a microporous layer (A) with good film-forming properties, productivity, thinness and low air permeability. A (Single layer Mt A ) is preferably 10 mN or more, more preferably 13 mN or more, even more preferably 16 mN or more, still more preferably 18 mN or more, and particularly preferably 19 mN or more, from the viewpoint of obtaining a microporous layer (A) with a higher pin puncture strength.
[0044] DSC parameters of the microporous layer (A) The microporous layer (A) preferably has an endothermic peak A having a peak value in the range of 100° C. to 145° C. and an endothermic peak B having a peak value in the range of 155° C. to 175° C. in a differential scanning calorimetry (DSC) curve (vertical axis indicates heat flow, horizontal axis indicates temperature) during the temperature rise process. A and the area S of endothermic peak B B Ratio to S B / S A is preferably 2 to 200. It is considered that endothermic peak A is derived from at least polyethylene among the components contained in the microporous layer (A), and endothermic peak B is derived from at least polypropylene among the components contained in the microporous layer (A). From the viewpoint of obtaining a microporous layer (A) with high pin puncture strength, the peak value range of endothermic peak A of the microporous layer (A) is preferably 100°C to 145°C, more preferably 110°C to 142°C, even more preferably 120°C to 140°C, and even more preferably 125°C to 135°C. From the viewpoint of obtaining a microporous layer (A) with high pin puncture strength and low air permeability, the peak value range of endothermic peak B of the microporous layer (A) is preferably 155°C to 175°C, more preferably 158°C to 173°C, even more preferably 160°C to 171°C, and even more preferably 163°C to 169°C. In addition, the S of the microporous layer (A) B / S A is considered to reflect the ratio of at least the polypropylene content to at least the polyethylene content, and from the viewpoint of maintaining good battery performance even after storage at high temperatures (e.g., 130°C) and maintaining good film-formability, puncture strength and air permeability, it is preferably 2 or more and 200 or less, more preferably 4 or more and 100 or less, even more preferably 6 or more and 50 or less, even more preferably 8 or more and 30 or less, and particularly preferably 10 or more and 25 or less.
[0045] <Area-average long pore diameter of the microporous layer (A)> The area average long pore diameter (hereinafter simply referred to as "area average long pore diameter") of the microporous layer (A) in the MD-ND cross section is preferably 50 nm or more and 500 nm or less. In the present disclosure, "ND" indicates the thickness direction of the microporous layer, and "MD" indicates the film formation direction of the microporous layer. For example, the MD of a separator having a microporous layer is the longitudinal direction if it is a roll. "Long pore diameter" means the pore diameter in MD. In addition, when there are two or more microporous layers (A) and / or microporous layers (B), the area average long pore diameters of the microporous layer (A) and the microporous layer (B) are compared based on the average area average long pore diameter value of each layer. The lower limit of the area average long pore diameter of the microporous layer (A) is preferably 50 nm or more, more preferably 80 nm or more, even more preferably 100 nm or more, still more preferably 120 nm or more, and particularly preferably 130 nm or more, from the viewpoint of ensuring high input / output in the electricity storage device and obtaining a microporous layer (A) with low air permeability. Also, the upper limit of the area average long pore diameter of the microporous layer (A) is preferably 500 nm or less, more preferably 400 nm or less, even more preferably 350 nm or less, still more preferably 300 nm or less, particularly preferably 250 nm or less, and most preferably 210 nm or less, from the viewpoint of obtaining a microporous layer (A) with high pin puncture strength.
[0046] The area-average pore size can be measured by observing the MD-ND cross section of the separator with a cross-sectional SEM (scanning electron microscope) and analyzing the image obtained in the range of MD 20 μm × ND 3 μm. Detailed conditions are shown in the Examples. When measuring the average pore size from the cross-sectional SEM image, the number-average pore size and the area-average pore size can be calculated, but in this disclosure, the area-average pore size is used as the average pore size so as to have a better correlation with the physical properties of the separator.
[0047] <Porosity of microporous layer (A)> The porosity of the microporous layer (A) is preferably 40% or more from the viewpoint of avoiding clogging in the electricity storage device and obtaining a microporous layer (A) with low air permeability, and is preferably 60% or less from the viewpoint of obtaining a microporous layer (A) with high pin puncture strength. The porosity of the microporous layer (A) is more preferably 43% to 57%, even more preferably 45% to 54%, and particularly preferably 47% to 53%.
[0048] <Thickness of microporous layer (A)> When the substrate of the electricity storage device separator has a single-layer structure having only one microporous layer (A), the upper limit of the thickness of the microporous layer (A) may be, from the viewpoint of increasing the energy density of the electricity storage device and reducing the air permeability of the microporous layer (A), preferably 20 μm or less, for example 18 μm or less, 16 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, or 10 μm or less. When the substrate has a single-layer structure, the lower limit of the thickness of the microporous layer (A) may be, from the viewpoint of obtaining a microporous layer (A) with high pin puncture strength, preferably 3 μm or more, for example 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, or 8 μm or more.
[0049] When the substrate of the separator for an electricity storage device has a multilayer structure including one or more microporous layers (A), the upper limit of the thickness of the microporous layer (A) may be preferably 10 μm or less, for example 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4.5 μm or less, or 4 μm or less, from the viewpoint of increasing the energy density of the electricity storage device and reducing the air permeability of the separator substrate. When the substrate has a multilayer structure, the lower limit of the thickness of the microporous layer (A) may be preferably 1 μm or more, for example 2 μm or more, 3 μm or more, or 3.5 μm or more, from the viewpoint of obtaining a separator substrate with high puncture strength.
[0050] Additives for the Microporous Layer (A) The microporous layer (A) mainly composed of polyolefin may further contain, in addition to polypropylene, polyethylene, and thermoplastic elastomer, additives such as elastomers, crystal nucleating agents, antioxidants, fillers, etc., as necessary. The amount of the additives is not particularly limited, and may be, for example, 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more, and may be, for example, 20% by mass or less, 10% by mass or less, or 7% by mass or less, based on the total mass of the microporous layer (A).
[0051] <Microporous layer (B)> The separator for an electric storage device of the present disclosure has a microporous layer (B) as desired. The separator for an electric storage device may have only one microporous layer (B) or two or more microporous layers. The microporous layer (B) is also mainly composed of polyolefin, more preferably polypropylene and / or polyethylene. This allows good pore opening and good battery performance to be obtained. The microporous layer (B) is more preferably mainly composed of polypropylene, which allows good battery performance to be maintained even after storage at high temperatures (e.g., 130°C). In the present disclosure, the microporous layer (B) being "mainly composed of" polypropylene means that the microporous layer (B) contains 50% by mass or more of polypropylene based on the total mass of the microporous layer (B). The lower limit of the polypropylene content in the microporous layer (B) may be preferably 55% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more from the viewpoint of the wettability of the separator, thinning, etc. The upper limit of the polypropylene content in the microporous layer (B) is not limited, and may be, for example, 98% by mass or less, 99% by mass or less, or 100% by mass.
[0052] <Material for the microporous layer (B)> The polypropylene of the microporous layer (B) may be the same material as the polypropylene of the microporous layer (A) described above, or may be a polypropylene having a different chemical structure, more specifically, a polypropylene having at least one different monomer composition, stereoregularity, molecular weight, and crystal structure. The stereoregularity of the polypropylene of the microporous layer (B) is not limited, but may be, for example, atactic, isotactic, or syndiotactic homopolymer. The polypropylene according to the present disclosure is preferably an isotactic or syndiotactic highly crystalline homopolymer.
[0053] The polypropylene of the microporous layer (B) is preferably a homopolymer, and may be a copolymer, such as a block polymer, in which a small amount of comonomer other than propylene, such as an α-olefin comonomer, is copolymerized. The amount of propylene structure contained as a repeating unit in the polypropylene is not limited, but may be, for example, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 99 mol% or more. The amount of repeating units derived from comonomers other than the propylene structure contained in the polypropylene is not limited, but may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less. The polypropylene may be used alone or in combination of two or more kinds.
[0054] The weight average molecular weight (Mw) of the polypropylene of the microporous layer (B) is preferably 250,000 or more from the viewpoint of the strength of the microporous layer, etc., and is preferably 1,000,000 or less from the viewpoint of increasing the pore size of the microporous layer and exhibiting good air permeability. The Mw of the polypropylene is more preferably 400,000 or more and 950,000 or less, even more preferably 550,000 or more and 900,000 or less, still more preferably 600,000 or more and 900,000 or less, and particularly preferably 700,000 or more and 900,000 or less.
[0055] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the polypropylene of the microporous layer (B) by the number average molecular weight (Mn) is preferably 7 or less, more preferably 6.5 or less, 6 or less, 5.5 or less, or 5 or less. The smaller the Mw / Mn value of the polypropylene, the smaller the melt tension of the obtained microporous layer tends to be. Therefore, it is preferable that the Mw / Mn value of the polypropylene is 7 or less in order to control the melt tension of the microporous layer (B) to be small. In addition, Mw / Mn may be preferably 1.1 or more, for example, 1.3 or more, 1.5 or more, 2.0 or more, or 2.5 or more. By having Mw / Mn of 1.1 or more, appropriate molecular entanglement is maintained, and stability during film formation may be improved. The weight average molecular weight, number average molecular weight, and Mw / Mn of the polyolefin in the microporous layer (B) of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement, similar to the case of the polypropylene in the microporous layer (A).
[0056] The density of the polypropylene of the microporous layer (B) is preferably 0.85 g / cm 3 For example, 0.88 g / cm 3 More than 0.89g / cm 3 or more than 0.90g / cm 3 The density of polypropylene is preferably 1.1 g / cm or more. 3 For example, 1.0 g / cm 3 Below, 0.98g / cm 3 Below, 0.97g / cm 3 Below, 0.96g / cm 3 Below, 0.95g / cm 3 Below, 0.94g / cm 3 Below, 0.93g / cm 3 or less than 0.92 g / cm 3 The density of polyolefins is related to the crystallinity of polypropylene, and the density of polypropylene can be less than 0.85 g / cm 3 By setting the above amount, the productivity of the microporous layer is improved, which is particularly advantageous in the dry method.
[0057] The microporous layer (B) may contain other resins in addition to polypropylene. Examples of other resins include polyolefins other than polypropylene (also referred to as "other polyolefins"). Polyolefins are polymers containing a monomer having a carbon-carbon double bond as a repeating unit. Monomers constituting polyolefins other than polypropylene are not limited, but include monomers having 2 or 4 to 10 carbon atoms and having a carbon-carbon double bond, such as ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene.
[0058] The microporous layer (B) may contain a thermoplastic elastomer other than polypropylene. The thermoplastic elastomer is not particularly limited, but examples thereof include polypropylene different from the main component, polyolefins other than polypropylene (also referred to as "other polyolefins"), and copolymers of polystyrene and polyolefin. Examples of polypropylene include low crystalline polypropylene having a low stereoregularity region. Polyolefin is a polymer containing a monomer having a carbon-carbon double bond as a repeating unit. Examples of monomers constituting polyolefins other than polypropylene include, but are not limited to, monomers having 2 or 4 to 10 carbon atoms having a carbon-carbon double bond, such as ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. The polyolefin is, for example, a homopolymer, a copolymer, or a multi-stage polymerization polymer, and as an example, polyethylene can be contained. Preferred examples of the copolymer of polystyrene and polyolefin include styrene-(ethylene-propylene)-styrene copolymer (SEPS), styrene-(ethylene-butene)-styrene copolymer (SEBS), hydrogenated-styrene-(ethylene-butene)-styrene copolymer (hydrogenated SEBS), styrene-ethylene-styrene copolymer, olefin crystal-(ethylene-butene)-olefin crystal copolymer (CEBC), hydrogenated-olefin crystal-(ethylene-butene)-olefin crystal copolymer (hydrogenated CEBC), styrene-(ethylene-butene)-olefin crystal copolymer (SEBC), hydrogenated-styrene-(ethylene-butene)-olefin crystal copolymer (hydrogenated SEBC), etc. Particularly preferred are hydrogenated-styrene-(ethylene-butene)-styrene copolymer (hydrogenated SEBS), hydrogenated-styrene-(ethylene-butene)-olefin crystal copolymer (hydrogenated SEBC), and styrene-(ethylene-propylene)-styrene copolymer (SEPS).
[0059] As the thermoplastic elastomer contained in the microporous layer (B), an elastomer incompatible with polypropylene is more preferable from the viewpoint of opening and increasing the pore size. The elastomer incompatible with polypropylene is not particularly limited, but preferably includes a copolymer of polyethylene and other polyolefins, and a copolymer of polystyrene and polyolefins. As the copolymer of polystyrene and polyolefin, preferably, styrene-(ethylene-propylene)-styrene copolymer (SEPS), styrene-(ethylene-butene)-styrene copolymer (SEBS), hydrogenated-styrene-(ethylene-butene)-styrene copolymer (hydrogenated SEBS), styrene-ethylene-styrene copolymer, olefin crystal-(ethylene-butene)-olefin crystal copolymer (CEBC), hydrogenated-olefin crystal-(ethylene-butene)-olefin crystal copolymer (hydrogenated CEBC), styrene-(ethylene-butene)-olefin crystal copolymer (SEBC), hydrogenated-styrene-(ethylene-butene)-olefin crystal copolymer (hydrogenated SEBC), etc. are mentioned. Particularly preferred are hydrogenated styrene-(ethylene-butene)-styrene copolymer (hydrogenated SEBS), hydrogenated styrene-(ethylene-butene)-olefin crystalline copolymer (hydrogenated SEBC), and styrene-(ethylene-propylene)-styrene copolymer (SEPS).
[0060] <Melt flow rate (MFR) of microporous layer (B)> The upper limit of the melt flow rate (MFR) of the microporous layer (B) (MFR of a single layer) is preferably 8.00 g / 10 min or less from the viewpoint of obtaining a microporous layer (B) with higher strength, and may be, for example, 6.00 g / 10 min or less, 4.00 g / 10 min or less, 3.00 g / 10 min or less, 2.00 g / 10 min or less, or 1.10 g / 10 min or less. The lower limit of the MFR of the microporous layer (B) (MFR of a single layer) is not limited from the viewpoint of exhibiting good air permeability, and may be, for example, 0.30 g / 10 min or more, 0.35 g / 10 min or more, 0.40 g / 10 min or more, 0.45 g / 10 min or more, or 0.50 g / 10 min or more. The MFR of the microporous layer (B) is measured under conditions of a load of 2.16 kg and a temperature of 230°C. The MFR of the microporous layer (B) being 8.00 g / 10 min or less means that the molecular weight of the polyolefin contained in the microporous layer (B) is significantly high. A high molecular weight polyolefin tends to produce a high-strength microporous layer (B) because there are more tie molecules that bond crystalline substances together. A microporous layer (B) having an MFR of 0.30 g / 10 min or more does not cause the melt tension of the microporous layer (B) to become too high, making it easier to produce a separator that exhibits good air permeability.
[0061] The MFR of the polypropylene of the microporous layer (B) is preferably 8.0 g / 10 min or less from the viewpoint of obtaining a microporous layer (B) with higher strength, and may be, for example, 6.0 g / 10 min or less, 4.0 g / 10 min or less, 3.0 g / 10 min or less, 2.0 g / 10 min or less, or 1.1 g / 10 min or less. The lower limit of the MFR of the microporous layer (B) (single layer MFR) is not limited from the viewpoint of exhibiting good air permeability, and may be, for example, 0.3 g / 10 min or more, 0.35 g / 10 min or more, 0.4 g / 10 min or more, 0.45 g / 10 min or more, or 0.5 g / 10 min or more.
[0062] The MFR of the microporous layer (B) is preferably higher than that of the microporous layer (A). By making the MFR of the microporous layer (B) higher than that of the microporous layer (A), the pore size of the microporous layer (B) in the obtained separator can be controlled to be larger than the pore size of the microporous layer (A).
[0063] <Pentad fraction of microporous layer (B)> From the viewpoint of obtaining a microporous layer with low air permeability, the lower limit of the pentad fraction of the polypropylene of the microporous layer (B) may be preferably 94.0% or more, for example, 95.0% or more, 96.0% or more, 96.5% or more, 97.0% or more, 97.5% or more, 98.0% or more, 98.5% or more, or 99.0% or more. The upper limit of the pentad fraction of the polypropylene is not limited, but may be 99.9% or less, 99.8% or less, or 99.5% or less. The pentad fraction of the polypropylene of the microporous layer (B) is, similarly to the case of the polypropylene of the microporous layer (A), 13 Measured by C-NMR (nuclear magnetic resonance).
[0064] A pentad fraction of 94.0% or more of the polypropylene in the microporous layer (B) indicates high crystallinity of the polypropylene. In a separator obtained by the stretching hole-opening method, particularly the dry method, the amorphous parts between the crystalline parts are stretched to open the holes, so if the polypropylene has high crystallinity, the hole-opening property is good and the air permeability can be kept low, which enables the battery to have high output.
[0065] <Melt tension of microporous layer (B)> Melt tension Mt of the microporous layer (B) at 240°C B The melt tension Mt is preferably 4 mN or more and 30 mN or less. B From the viewpoint of good film-forming properties and productivity of the separator substrate having the microporous layer (A) and the microporous layer (B), the lower limit of the melt tension Mt is preferably 4 mN or more, more preferably 7 mN or more, even more preferably 10 mN or more, particularly preferably 13 mN or more, and most preferably 16 mN or more. B From the viewpoint of achieving a large pore diameter and exhibiting good air permeability, the upper limit of the melt tension Mt of the microporous layers (A) and (B) at a temperature of 240° C. is preferably 30 mN or less, more preferably 28 mN or less, even more preferably 26 mN or less, and most preferably 24 mN or less. A and Mt. Bmay be different from each other from the viewpoint of the area average long pore diameter of the microporous membrane.
[0066] <Area-average long pore diameter of microporous layer (B)> The area average long pore diameter (hereinafter also simply referred to as "area average long pore diameter") in the MD-ND cross section of the microporous layer (B) is preferably larger than the area average long pore diameter of the microporous layer (A). For details of the relationship with the area average long pore diameter of the microporous layer (A), please refer to the section "Area average long pore diameter of the microporous layer (A)".
[0067] The area average long pore diameter of the microporous layer (B) in the MD-ND cross section is preferably 100 nm to 600 nm, more preferably 120 nm to 500 nm, even more preferably 140 nm to 400 nm, and still more preferably 160 nm to 350 nm. When the area average long pore diameter of the microporous layer (B) is within this range, good pin puncture strength and air permeability can be obtained.
[0068] <Porosity of microporous layer (B)> The porosity of the microporous layer (B) is preferably 20% or more from the viewpoint of avoiding clogging in the electricity storage device and obtaining good air permeability of the separator, and is preferably 70% or less from the viewpoint of maintaining the strength of the separator. The porosity of the microporous layer (B) is more preferably 25% to 65%, further preferably 30% to 60%, and particularly preferably 35% to 60%.
[0069] <Thickness of microporous layer (B)> The thickness of the microporous layer (B) may be preferably 10 μm or less, for example, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4.5 μm or less, or 4 μm or less, from the viewpoint of increasing the energy density of the electricity storage device, etc. The lower limit of the thickness of the microporous layer (B) may be preferably 1 μm or more, for example, 2 μm or more, 3 μm or more, or 3.5 μm or more, from the viewpoint of strength, etc.
[0070] Additives for the Microporous Layer (B) In addition to the polyolefin, the microporous layer (B) may further contain additives such as elastomers, crystal nucleating agents, antioxidants, fillers, etc., as necessary. The amount of the additives is not particularly limited, and may be, for example, 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more, and may be, for example, 10% by mass or less, 7% by mass or less, or 5% by mass or less, based on the total mass of the microporous layer (B).
[0071] <Relationship between microporous layer (A) and microporous layer (B)> Melt tension Mt of the microporous layer (A) at 240°C A and the melt tension Mt of the microporous layer (B) at 240°C. B Compared to Mt A / Mt B is preferably 1.05 or more and 4.0 or less. A / Mt B By making the Mt equal to or greater than 1.05, the pore size of the microporous layer (A) of the obtained separator can be controlled to be sufficiently small and the pore size of the microporous layer (B) can be controlled to be sufficiently large, thereby achieving both good voltage resistance and air permeability. A / Mt B By making Mt 4.0 or less, it is possible to obtain a separator having good pore opening and air permeability. A / Mt B is more preferably 1.1 or more and 3.5 or less, even more preferably 1.15 or more and 3.3 or less, still more preferably 1.2 or more and 3.0 or less, and particularly preferably 1.25 or more and 2.5 or less.
[0072] MFR of microporous layer (B) B ) and the MFR of the microporous layer (A) (MFR A ) ratio, MFR B / MFR A The MFR is preferably 1.02 or more and 10.0 or less. B / MFR A By making the MFR equal to or greater than 1.02, the pore size of the microporous layer (A) of the obtained separator can be controlled to be sufficiently small and the pore size of the microporous layer (B) can be controlled to be sufficiently large, thereby achieving both good voltage resistance and air permeability. B / MFR ABy making the MFR equal to or less than 10.0, it is possible to obtain a separator having stable membrane-forming properties, productivity, and good pore opening and air permeability. B / MFR A is more preferably 1.05 or more and 6.0 or less, even more preferably 1.1 or more and 5.0 or less, still more preferably 1.1 or more and 4.0 or less, and particularly preferably 1.1 or more and 3.0 or less.
[0073] Weight average molecular weight Mw of polypropylene of microporous layer (A) A and the weight average molecular weight Mw of the polypropylene of the microporous layer (B) B Ratio of Mw A / Mw B is preferably 1.02 or more and 2.0 or less. A / Mw B By making the melt tension ratio Mt A / Mt B As a result, it is possible to effectively suppress dendrite formation in the power storage device. A / Mt B By making the Mw 2.0 or less, it is possible to obtain a separator having stable film-forming properties, productivity, and good pore opening and air permeability. A / Mw B is preferably 1.02 or more and 1.8 or less, more preferably 1.03 or more and 1.6 or less, and most preferably 1.05 or more and 1.4 or less.
[0074] <Layer structure of separator substrate> The substrate of the separator for an electric storage device (also simply referred to as "separator substrate" in the present disclosure) may be a microporous body used in the separator for an electric storage device, and may have a single-layer structure of only a microporous layer (A), or may have a multilayer structure having at least one microporous layer (A). In addition, it may have a multilayer structure having at least one microporous layer (A) and at least one microporous layer (B). Furthermore, the separator substrate may have a multilayer structure of three or more layers having at least two layers of at least one of the microporous layer (A) and / or the microporous layer (B). For example, a two-layer structure of microporous layer (A) / microporous layer (B) and a three-layer structure of microporous layer (A) / microporous layer (B) / microporous layer (A) may be mentioned. In addition, the separator substrate may have layers other than the microporous layer (A) and the microporous layer (B). For example, the layers other than the microporous layer (A) and the microporous layer (B) may include, for example, a microporous layer mainly composed of a polyolefin other than (A) and (B), a layer containing an inorganic substance, and a layer containing a heat-resistant resin. In addition, the separator substrate may have a multilayer structure of four or more layers, such as microporous layer (A) / microporous layer (B) / microporous layer (C) / microporous layer (A). From the viewpoints of ease of production and suppression of curling of the separator, a symmetrical laminate structure is preferred.
[0075] <Thickness of separator substrate> The upper limit of the thickness of the separator substrate is preferably 20 μm or less, for example, 18 μm or less, 16 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, or 10 μm or less, from the viewpoint of increasing the energy density and increasing the input / output of the power storage device. The lower limit of the thickness of the separator substrate is preferably 3 μm or more, for example, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, or 8 μm or more, from the viewpoint of obtaining a microporous layer (A) with high pin puncture strength.
[0076] <Air permeability (air resistance) of separator substrate> The upper limit of the air permeability of the separator substrate is preferably 400 sec / 100 cm from the viewpoint of ensuring a good output in the power storage device. 3 Less than 350 seconds / 100 cm, more preferably 350 seconds / 100 cm 3Less than 300 seconds / 100 cm, more preferably 300 seconds / 100 cm 3 More preferably, 250 seconds / 100 cm or less 3 Below 220 seconds / 100 cm, particularly preferred 3 Below 200 seconds / 100 cm, most preferably 3 The lower limit of the air permeability of the separator substrate is not limited, but is, for example, 10 sec / 100 cm 3 Over 20 seconds / 100cm 3 or more, or 30 seconds / 100cm 3 It may be more than that.
[0077] <Porosity of separator substrate> The porosity of the separator substrate is preferably 40% or more from the viewpoint of avoiding clogging in the power storage device and obtaining good air permeability of the separator, and is preferably 60% or less from the viewpoint of maintaining the puncture strength of the separator. The porosity of the separator substrate is more preferably 43% to 57%, further preferably 45% to 54%, and particularly preferably 47% to 53%.
[0078] <Puncture strength of separator substrate> The lower limit of the puncture strength of the separator substrate, when converted to a thickness of 10 μm, is preferably 150 gf or more (about 1.47 N or more), more preferably 180 gf or more, 200 gf or more, 220 gf or more, or 240 gf or more, and particularly preferably 260 gf or more, 270 gf or more, or 280 gf or more. The upper limit of the puncture strength of the separator substrate is not limited, but may be preferably 500 gf or less, for example 450 gf or less, or 400 gf or less, when converted to a thickness of 10 μm.
[0079] <Thermal shrinkage rate of separator substrate> The separator substrate preferably has a thermal shrinkage rate in the transverse direction (TD) of 5% or less after heat treatment at a temperature of 105°C for 1 hour, and more preferably -1.0% or more and 3.0% or less. That is, a separator substrate having a TD thermal shrinkage rate of 5% or less at 105°C means that the thermal shrinkage rate in the TD is very small even at high temperatures. The thermal shrinkage rate of 5% or less or 3.0% or less can effectively suppress short circuits at high temperatures. The reason why the thermal shrinkage rate is -1.0% or more is that when the thermal shrinkage rate is measured, the substrate expands in the TD, and the thermal shrinkage rate may become a negative value less than 0%. The thermal shrinkage rate may be 0% or more, or may be greater than 0%. Examples of methods for producing a separator substrate having a thermal shrinkage rate of 5% or less or -1.0% or more and 3.0% or less include, for example, a method for producing a separator by uniaxial stretching in the MD, and preferably a method for producing a separator by a dry method of uniaxial stretching. In a separator manufacturing method using biaxial stretching in MD and TD, as typified by a wet separator, the thermal shrinkage in TD is generally very large, whereas in a uniaxially stretched dry separator, it is easy to obtain a separator substrate having a thermal shrinkage rate of 5% or less, or -1.0% or more and 3.0% or less.
[0080] The separator substrate has a heat shrinkage in the film formation direction (MD) after heat treatment at a temperature of 105° C. for 1 hour, from the viewpoint of productivity of the power storage device and suppression of short circuits at high temperatures, of preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 8% or less, particularly preferably 6% or less, and most preferably 5.5% or less. The lower limit of the heat shrinkage is not limited, but may be preferably 0.1% or more, for example, 0.3% or more, or 0.5% or more. In the separator substrate of the present disclosure, as described above, when the separator substrate is produced by uniaxial stretching in the MD and the microporous layer (A) has parallel connection domains in the MD, it is possible to relax the stress applied to the polymer matrix even during heat shrinkage in the MD, and it is believed that a low MD heat shrinkage can be achieved.
[0081] The separator substrate preferably has a MD tensile strength of 1500 kgf / cm from the viewpoints of ease of operation during battery winding and high puncture strength. 2or more (approximately 14.7kN / cm 2 or more), more preferably 1600kgf / cm 2 More preferably, 1700 kgf / cm 2 More preferably, 1800 kgf / cm 2 More than 1900kgf / cm 2 The upper limit of the tensile strength in the MD of the separator substrate is not limited, but is preferably 4000 kgf / cm 2 For example, 3800kgf / cm 2 Below 3500kgf / cm 2 Below, 3200kgf / cm 2 or less than 3000kgf / cm 2 It may be the following:
[0082] From the viewpoint of productivity and high pin puncture strength of the power storage device, the MD tensile elongation of the separator substrate is preferably 20% or more, more preferably 24% or more, even more preferably 26.5% or more, even more preferably 28% or more, and particularly preferably 30% or more. From the viewpoint of processability, the upper limit of the MD tensile elongation of the separator substrate is preferably 60% or less, more preferably 55% or less, even more preferably 50% or less, even more preferably 45% or less, and particularly preferably 40% or less. In the separator substrate of the present disclosure, as described above, when the separator substrate is produced by uniaxial stretching in MD and the microporous layer (A) has a connected domain in parallel in MD, it is possible to relax the stress applied to the polymer matrix even during tension in MD, and it is considered that a high MD tensile elongation can be realized.
[0083] <<Method for producing separator for power storage device>> The method for producing a separator for an electricity storage device includes a melt extrusion step of melt extruding a resin composition mainly composed of polypropylene (hereinafter also referred to as a "polypropylene-based resin composition") to obtain a resin sheet (precursor sheet), and a hole forming step of opening holes in the obtained precursor sheet to make it porous. The method for producing a microporous layer is roughly divided into a dry method in which no solvent is used in the hole forming step, and a wet method in which a solvent is used.
[0084] Examples of the dry method include a method in which a polypropylene-based resin composition is melt-kneaded and extruded, and then the polypropylene crystal interface is peeled off by heat treatment and stretching; and a method in which a polypropylene-based resin composition and an inorganic filler are melt-kneaded and formed into a film, and then the interface between the polypropylene and the inorganic filler is peeled off by stretching.
[0085] Examples of the wet method include a method in which a polypropylene resin composition and a pore-forming material are melt-kneaded to form a film, which is then stretched as necessary, and the pore-forming material is extracted; and a method in which the polypropylene resin composition is dissolved, and then the film is immersed in a poor solvent for polypropylene to solidify the polypropylene and simultaneously remove the solvent.
[0086] For melt-kneading of the polypropylene-based resin composition, a single screw extruder or a twin screw extruder can be used. In addition to these, for example, a kneader, a Labo Plastomill, a kneading roll, a Banbury mixer, etc. can also be used.
[0087] The polypropylene resin composition may contain, as desired, a resin other than polypropylene, an additive, etc., depending on the method for producing the microporous layer or the physical properties of the intended microporous layer. Examples of the additives include a pore-forming material, a fluorine-based flow modifier, a wax, a crystal nucleating material, an antioxidant, a metal soap such as an aliphatic carboxylic acid metal salt, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a coloring pigment. Examples of the pore-forming material include a plasticizer, an inorganic filler, or a combination thereof.
[0088] Examples of the plasticizer include hydrocarbons such as liquid paraffin and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol.
[0089] Examples of inorganic fillers include oxide ceramics such as alumina, silica (silicon oxide), titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers.
[0090] A preferred method for producing the separator substrate is a dry lamellar crystal opening process in which the polypropylene crystal interface is peeled off by heat treatment and stretching. Here, a preferred method for producing the separator substrate having the microporous layer (A) and the microporous layer (B) is at least one of the following methods (i) and (ii): (i) a method for producing a separator substrate by coextrusion, comprising coextrusion forming a microporous layer (A) and a microporous layer (B), followed by annealing, cold stretching, hot stretching and heat relaxation; and (ii) A method for producing a separator substrate by lamination, in which the microporous layer (A) and the microporous layer (B) are separately extruded and laminated together, followed by annealing, cold stretching, hot stretching and heat relaxation.
[0091] Of the above coextrusion process (i) and lamination process (ii), the coextrusion process (i) is preferred from the viewpoint of production costs, etc. In the coextrusion process (i), the extrusion film formation conditions for the microporous layers (A) and (B) are preferably such that the resin is discharged at the lowest possible temperature and effectively quenched by blowing low-temperature air. After film formation, it is preferable to quench with air, and the temperature of the blown air is preferably 20°C or lower, more preferably 15°C or lower. By blowing cold air controlled at such a low temperature, the resin after film formation is uniformly oriented in the MD.
[0092] In both the co-extrusion process (i) and the lamination process (ii), the method for producing the separator substrate may include an annealing step after extrusion film formation. By carrying out the annealing step, the crystal structure of the microporous layers (A) and (B) grows, and the pore opening tends to be improved. By providing annealing at a specific temperature for a predetermined time, it tends to be possible to obtain a good area average long pore diameter, high porosity, low air permeability, and high pin puncture strength for both the microporous layers (A) and (B). The reason for this is considered to be that the crystals grow without disturbing the crystal structure, and high pore opening is obtained. In the annealing step, the annealing treatment is preferably performed at a temperature range of 115°C to 160°C, more preferably 135°C to 160°C, and preferably for 20 minutes or more, more preferably 60 minutes or more. This is preferable from the viewpoint of obtaining a good area average long pore diameter, high porosity, low air permeability, and high pin puncture strength, and expressing high input / output and high energy density of the electricity storage device.
[0093] The method for producing the separator substrate may include a stretching step after the annealing step. As the stretching process, either uniaxial stretching or biaxial stretching may be used. Although not limited, uniaxial stretching is preferred from the viewpoint of production costs when using a dry method and reduction of thermal shrinkage in TD. The MD stretching ratio of cold stretching ((dimension after stretching-dimension before stretching) / dimension before stretching x 100 (%)) is preferably in the range of 5% to 50%, more preferably 20% to 45%, and even more preferably 25% to 45%. By increasing the amount of cracks generated during cold stretching, it is easy to obtain a small pore diameter during hot stretching, and a separator with high puncture strength can be obtained. The temperature of cold stretching is preferably 10°C to 50°C, more preferably 20°C to 30°C, and may be performed at room temperature (23±2°C) from the viewpoint of production costs. From the viewpoints of improving both the puncture strength and low air permeability of the resulting separator substrate, production costs, and reducing TD heat shrinkage, uniaxial stretching is preferred.
[0094] In order to suppress the thermal shrinkage of the separator substrate, a heat treatment step may be performed for the purpose of heat setting after the stretching step or the hole formation step. The heat treatment step may include a hot stretching operation performed at a predetermined temperature and a predetermined stretch ratio for the purpose of adjusting physical properties, and / or a heat relaxation operation performed at a predetermined temperature and a predetermined relaxation ratio for the purpose of reducing the shrinkage stress imparted during film formation and stretching. A heat relaxation operation may be performed after the hot stretching operation. In the hot stretching and heat relaxation, the MD dimension before stretching is taken as 100%, and the film is stretched preferably to 140% to 280%, more preferably to 160% to 260%, and even more preferably to 180% to 240%, and then relaxed in the MD by preferably 10% to 50%, more preferably 20% to 45%. These heat treatment steps can be performed using a tenter or a roll stretching machine. The temperature of the heat treatment step is preferably 120°C to 160°C, and even more preferably 130°C to 155°C.
[0095] From the viewpoint of achieving both high puncture strength and low air permeability in the thin-film separator, and from the viewpoint of obtaining a morphology such as that shown in FIG. 1, it is preferable to carry out the above-mentioned annealing treatment and hot stretching operation in the method for producing the separator. From these viewpoints, in another embodiment of the present disclosure, the following steps are carried out: An annealing step of annealing a resin sheet containing polypropylene, polyethylene, and a thermoplastic elastomer at a temperature of 135°C or more and 160°C or less; and A heat treatment step of stretching the annealed resin sheet in MD at a temperature of 130°C or more and 155°C or less; The resin sheet, the annealing conditions, and the heat treatment conditions involving the hot stretching operation may be as described above.
[0096] The obtained separator substrate can be used as it is as a separator for an electricity storage device. Optionally, one or both sides of the separator substrate may be provided with a further layer, such as a coating layer, and if necessary, a surface treatment, such as a corona treatment, may be performed.
[0097] <Electricity storage device> The power storage device of the present disclosure includes the separator for the power storage device of the present disclosure. The power storage device of the present disclosure preferably has a positive electrode and a negative electrode, and the separator for the power storage device of the present disclosure is preferably disposed between the positive electrode and the negative electrode.
[0098] Examples of the power storage device include, but are not limited to, lithium secondary batteries (including all-solid-state lithium batteries, lithium-sulfur batteries, and lithium-air batteries), lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel-hydrogen batteries, nickel-cadmium batteries, electric double-layer capacitors, lithium ion capacitors, redox flow batteries, and zinc-air batteries. Among these, from the viewpoints of high energy density, low cost, and durability, lithium secondary batteries, lithium ion secondary batteries, and lithium ion capacitors are preferred, and lithium ion secondary batteries are more preferred.
[0099] The electricity storage device can be produced, for example, by stacking a positive electrode and a negative electrode with the separator described above interposed therebetween and winding them as necessary to form a laminated electrode body or a wound electrode body, which is then loaded into an outer casing, connecting the positive and negative electrodes to the positive and negative electrode terminals of the outer casing via a lead body or the like, and further injecting a nonaqueous electrolyte solution containing a nonaqueous solvent such as a chain or cyclic carbonate and an electrolyte such as a lithium salt into the outer casing and then sealing the outer casing.
[0100] The present power storage device is more preferably a lithium ion secondary battery, and preferred embodiments of the lithium ion secondary battery will now be described.
[0101] The positive electrode is not particularly limited as long as it functions as a positive electrode of a lithium ion secondary battery, and a known positive electrode can be used. The positive electrode preferably contains one or more materials selected from the group consisting of materials capable of absorbing and releasing lithium ions as a positive electrode active material. From the viewpoint of battery capacity and safety, the positive electrode is preferably made of lithium cobalt oxide represented by LiCoO2, spinel lithium manganese oxide represented by Li2Mn2O4, or lithium manganese oxide represented by Li2Mn 1.5 Ni 0.5 Examples of the lithium-containing composite metal oxide include a spinel-type lithium nickel manganese oxide represented by LiCoO4, a lithium nickel oxide represented by LiNiO2, a lithium-containing composite metal oxide represented by LiMO2 (M represents two or more elements selected from the group consisting of Ni, Mn, Co, AI, and Mg), and a lithium iron phosphate compound represented by LiFePO4. Among these, from the viewpoint of high safety and long-term stability, more preferred are a lithium cobalt oxide represented by LiCoO2, a lithium nickel oxide represented by LiNiO2, a lithium-containing composite metal oxide represented by LiMO2 (M represents two or more elements selected from the group consisting of Ni, Mn, Co, AI, and Mg), and a lithium iron phosphate compound represented by LiFePO4, and a lithium iron phosphate compound represented by LiFePO4 is particularly preferred.
[0102] The negative electrode is not particularly limited as long as it acts as the negative electrode of the lithium ion secondary battery, and may be a known one. The negative electrode preferably contains one or more materials selected from the group consisting of materials capable of absorbing and releasing lithium ions and metallic lithium as the negative electrode active material. That is, the negative electrode preferably contains one or more materials selected from the group consisting of metallic lithium, carbon materials, materials containing elements capable of forming an alloy with lithium, and lithium-containing compounds as the negative electrode active material. Examples of such materials include, in addition to metallic lithium, hard carbon, soft carbon, artificial graphite, natural graphite, graphite, pyrolytic carbon, coke, glassy carbon, baked bodies of organic polymer compounds, mesocarbon microbeads, carbon fibers, activated carbon, graphite, carbon colloids, and carbon black. EXAMPLES
[0103] Measurement and evaluation methods [Melt flow rate (MFR) measurement] The melt flow rates (MFR) of the microporous layer (A) and the microporous layer (B) were measured at a temperature of 230°C and a load of 2.16 kg (unit: g / 10 min) in accordance with JIS K 7210. The MFR of the polypropylene or elastomer was measured at a temperature of 230°C and a load of 2.16 kg in accordance with JIS K 7210. The melt flow rate (MFR) of the polyethylene was measured at a temperature of 190°C and a load of 2.16 kg in accordance with JIS K 7210.
[0104] [Measurement of Mw and Mn by GPC (gel permeation chromatography)] A calibration curve was prepared by measuring standard polystyrene under the following conditions using an Agilent PL-GPC220. Chromatography was also performed on the sample polymer or microporous layer under the same conditions, and the polystyrene-equivalent weight average molecular weight (Mw), number average molecular weight (Mn), and MWD (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn) of the polymer or microporous layer were calculated based on the calibration curve under the following conditions. Column: TSKgel GMHHR-H(20) HT (7.8mmI.D.×30 cm) x 2 Mobile phase: 1,2,4-trichlorobenzene Detector: RI Column temperature: 160℃ Sample concentration: 1mg / ml Calibration curve: Polystyrene
[0105] [Melt tension measurement] The melt tension (mN) of the microporous layer (A) and the microporous layer (B) was measured under the following conditions using a Capillograph manufactured by Toyo Seiki Seisakusho. Capillary: diameter 1.0mm, length 20mm Cylinder extrusion speed: 2mm / min Take-off speed: 60m / min ·Temperature: 240℃
[0106] [Measurement of pentad fraction] The pentad fraction of polypropylene was assigned based on the description in the Polymer Analysis Handbook (edited by the Japan Society for Analytical Chemistry). 13 The values were calculated from the C-NMR spectrum by the peak height method. 13 The C-NMR spectrum was measured using a JEOL-ECZ500 by dissolving polypropylene pellets in o-dichlorobenzene-d at a measurement temperature of 145°C and 25,000 cumulative cycles.
[0107] [DSC Measurement] The microporous layer (A) was subjected to DSC measurement using a Shimadzu DSC-60 under the following conditions. Sample size: Approx. 5 mg Cell used: Aluminum crimp cell (diameter: 5.8mm) Operating atmosphere: Nitrogen (flow rate 50mL / min) Temperature Program: 1st step: Heat from room temperature to 230°C at 10°C / min and hold for 5 min 2nd step: Decrease temperature to 20°C at 10°C / min and hold for 5 min 3rd step: Raise temperature to 200°C at 10°C / min and hold for 5 min From the DSC curve (vertical axis is heat flow, horizontal axis is temperature) during the heating process in the third step, the peak temperatures of endothermic peaks A and B are read using the analysis software TA-60 attached to the device, and the area S of endothermic peak A is calculated. A and the area S of endothermic peak B B Calculate and S B / S A asked for.
[0108] [Measurement of thickness (μm)] The thickness (μm) of the separator substrate was measured using a Mitutoyo Digimatic Indicator IDC112 at room temperature of 23±2° C. The thickness of each microporous layer was calculated from cross-sectional SEM image data obtained by the evaluation method for the area average long pore diameter described below.
[0109] [Measurement of porosity (%)] A sample measuring 10 cm x 10 cm square was cut from the separator or microporous layer, and its volume (cm 3 ) and mass (g), and then calculate the density (g / cm 3 ) the porosity was calculated using the following equation. Porosity (%) = (volume-mass / density) / volume x 100
[0110] [Air permeability (sec / 100cm) 3 )] The air permeability (sec / 100cm) of the separator substrate was measured using a Gurley air permeability meter conforming to JIS P-8117. 3 ) was measured. 3 ) by the separator substrate thickness (μm) and multiplying it by 10 μm to obtain the air permeability (sec / 100 cm) when the separator substrate thickness is converted to 10 μm. 3 -10μm) was also obtained.
[0111] [MD heat shrinkage rate (%), TD heat shrinkage rate (%)] The separator substrate was cut into 50 mm squares in both MD and TD, and the resulting samples were placed on copy paper in a hot air dryer (Yamato Scientific Co., Ltd., DF1032) and heat-treated at normal pressure and in air at 105°C for 1 hour. The sample was removed from the hot air dryer and allowed to cool at 25°C for 10 minutes, after which the dimensional shrinkage was determined. Heat shrinkage rate (%): (dimension before heating (mm) - dimension after heating (mm)) / (dimension before heating (mm)) x 100
[0112] [Piercing strength] A needle with a hemispherical tip with a radius of 0.5 mm was prepared, and the separator was sandwiched between two plates with an opening of a diameter (dia.) of 11 mm, and the needle, separator, and plates were set. A puncture test was performed using Imada Co., Ltd.'s "MX2-50N" under the conditions of a needle tip curvature radius of 0.5 mm, a separator holding plate opening diameter of 11 mm, and a puncture speed of 25 mm / min. The needle and separator were brought into contact with each other, and the maximum puncture load (i.e., puncture strength (gf)) was measured. The puncture strength (gf) was divided by the separator substrate thickness (μm) and multiplied by 10 μm to obtain the puncture strength (gf / 10 μm) when the thickness of the separator substrate was converted to 10 μm.
[0113] [MD tensile strength, MD tensile elongation] The tensile strength of the separator was measured using a tensile tester (TG-1kN type manufactured by Minebea Co., Ltd.) by setting the length of the sample before the test to 35 mm and pulling the sample at a speed of 100 mm / min. The tensile strength (kgf / cm2) was calculated by dividing the strength (tensile load value) when the sample yielded, or the strength (tensile load value) when the sample broke (fractured) before yielding, by the cross-sectional area of the test piece. 2 The elongation at which the sample broke (the percentage of elongation from before the test) was taken as the tensile elongation (%). The tensile strength and tensile elongation were measured in the MD direction of the separator.
[0114] [Area average long pore diameter (nm)] The area-average long pore diameter was measured by image analysis of cross-sectional SEM observation. As a pretreatment, the separator was stained with ruthenium, and a cross-sectional sample was prepared by freeze fracturing. The cross section was the MD-ND surface. The cross-sectional sample was fixed to a cross-sectional observation SEM sample stage with a conductive adhesive (carbon-based) and dried, and then osmium coating was performed as a conductive treatment using an osmium coater (HPC-30W, manufactured by Vacuum Device Co., Ltd.) under the conditions of an applied voltage adjustment knob setting of 4.5 and a discharge time of 0.5 seconds, and a microscopic specimen was obtained. Next, a scanning electron microscope (Hitachi High-Technologies S-4800) was used to observe three arbitrary points on the microporous membrane surface under the conditions of an acceleration voltage of 1 kV, a detection signal of LA10, a working distance of 5 mm, and a magnification of 5000 times.
[0115] The observed images were binarized using the image processing software ImageJ using the Otsu method, the resin part and the hole part were separated, and the average long diameter of the hole part was calculated. At this time, the hole area existing between the photographed range and outside the photographed range was 0.001 nm 2 The following pores were excluded from the measurement: The average diameter was calculated by averaging the area of each pore.
[0116] Example 1 [Preparation of polypropylene resin composition] Pellets of high molecular weight polypropylene resin (PP1, MFR = 0.51), high molecular weight polyethylene resin (PE1, MFR = 0.02) and ethylene / propylene copolymer (C2C3, MFR = 9.5) shown in Table 1 were dry blended in a mass ratio of PP1:PE1:C2C3 = 74.2:13.8:12.0 (mass%), and then melt-kneaded using TEM26SS (Toshiba Machine Co., Ltd., L / D = 48.5). After melt-kneading, strands were pulled from a die (3 holes) and cooled in a water-cooled bath, and then cut using a pelletizer to obtain polypropylene resin composition pellets.
[0117] [Preparation of microporous layer] As the resin for the microporous layer (A), a high molecular weight polypropylene resin (PP1, MFR = 0.51) shown in Table 1 and the above polypropylene resin composition pellets were dry blended in a mass ratio of PP1: polypropylene resin composition pellets = 73.0: 27.0 (mass%), then melted in a 2.5-inch extruder and fed to a single-layer inflation die using a gear pump. The temperature of the inflation die was set to 240 ° C., and the molten polymer was discharged from the inflation die, and then the discharged resin was cooled by blown air and wound up on a roll to obtain a precursor sheet with a single-layer structure consisting of a microporous layer (A) with a thickness of about 12 μm. Here, the lip distance (lip clearance) of the inflation die was set to 1.8 mm, and discharge was performed under the discharge amount condition of 9 kg / h.
[0118] The obtained precursor sheet was then placed in a dryer and annealed at 150°C for 180 minutes. The annealed precursor sheet was then cold stretched 40% in MD at room temperature, and the stretched film was placed in an oven at 135°C without shrinking, and hot stretched to 220% in MD with the dimensions before stretching set to 100%, and then thermally relaxed 44% in MD to obtain a separator substrate having a single layer structure consisting of a microporous layer (A). The structure and physical properties of the obtained separator substrate are shown in Table 1.
[0119] The lower limit thickness of the precursor sheet was obtained by manufacturing a precursor sheet with a thickness of about 12 μm, gradually increasing the take-up speed while keeping the discharge amount constant to thin the sheet, and measuring the thickness just before the sheet ruptures. The obtained precursor sheet with the lower limit thickness was stretched and opened under the above annealing and stretching conditions (annealing at 150° C. for 180 minutes, cold stretching at room temperature by 40%, hot stretching at 135° C. to 220%, and relaxing by 44%) to obtain a separator substrate having a single layer structure, and measuring the thickness to obtain the lower limit thickness of the separator. The results are shown in Table 1.
[0120] Examples 2 to 14, Comparative Example 3 A separator substrate having a single layer structure was obtained in the same manner as in Example 1, except that the raw materials were changed as shown in Table 1, the mass ratio of the polypropylene resin and the polypropylene resin composition pellets was adjusted as shown in Table 1, and the die and the extrusion temperature at which extrusion was stable were finely adjusted. The evaluation results of the obtained separator substrate are shown in Table 1.
[0121] Comparative Examples 1 and 4 A separator substrate having a single layer structure was obtained in the same manner as in Example 1, except that a polypropylene resin composition was not prepared, and 100% by mass of a high molecular weight polypropylene resin shown in Table 1 was melted in a 2.5-inch extruder as the resin for the microporous layer (A), and the extrusion temperature at which the die and extrusion were stable was finely adjusted. The evaluation results of the obtained separator substrate are shown in Table 1.
[0122] Comparative Example 2 In preparing the polypropylene resin composition, pellets of a high molecular weight polypropylene resin (PP1, MFR = 0.51) and a high molecular weight polyethylene resin (PE1, MFR = 0.02) shown in Table 1 were dry-blended in a mass ratio of PP1:PE1 = 84.3:15.7 (mass%), and as the resin of the microporous layer (A), pellets of a high molecular weight polypropylene resin (PP1, MFR = 0.51) and a polypropylene resin composition shown in Table 1 were dry-blended in a mass ratio of PP1:polypropylene resin composition pellets = 75.8:24.2 (mass%), and a separator substrate having a single layer structure was obtained according to the same method as in Example 1, except that the die and the extrusion temperature at which the extrusion was stable were finely adjusted. The evaluation results of the obtained separator substrate are shown in Table 1.
[0123] Example 15 [Preparation of polypropylene resin composition] The pellets were obtained according to the same method as in Example 1.
[0124] [Preparation of microporous layer] As the resin for the microporous layer (A), the high molecular weight polypropylene resin (PP1, MFR = 0.51) shown in Table 1 and the above pellets were dry-blended in a mass ratio of PP1:pellets = 73.0:27:0 (mass%), and then melted in a 2.5-inch extruder and supplied to both outer layers of the two-kind, three-layer co-extrusion inflation die using a gear pump. As the resin for the microporous layer (B), 100 mass% of a high molecular weight polypropylene resin (PP3, MFR = 0.31) was melted in a 2.5-inch extruder and supplied to the inner layer of the two-kind, three-layer co-extrusion inflation die using a gear pump. The temperature of the inflation die was set to 235 ° C., and the molten polymer was discharged from the inflation die, and the discharged resin was cooled by blown air while being wound on a roll to obtain a precursor sheet with an A / B / A layer structure of about 12 μm in thickness. Here, the lip distance (lip clearance) of the inflation die was set to 1.8 mm, and extrusion was performed at an extrusion rate of 9 kg / h. Next, annealing, cold stretching, hot stretching, and thermal relaxation were performed in the same manner as in Example 1 to obtain a separator substrate having a three-layer structure of microporous layer (A) / microporous layer (B) / microporous layer (A). The obtained separator was evaluated. The evaluation results are shown in Table 1. The lower limit thicknesses of the precursor sheet and the separator were determined in the same manner as in Example 1, and the obtained results are shown in Table 1.
[0125] Comparative Example 5 A separator substrate having a three-layer structure of microporous layer (A) / microporous layer (B) / microporous layer (A) was obtained in the same manner as in Example 15, except that a polypropylene resin composition was not prepared, and 100% by mass of the high molecular weight polypropylene resin shown in Table 1 was melted in a 2.5-inch extruder as the resin for the microporous layer (A), and the extrusion temperature at which the die and extrusion were stable was finely adjusted. The evaluation results of the obtained separator substrate are shown in Table 1.
[0126] [Table 1-1]
[0127] [Table 1-2] [Industrial Applicability]
[0128] The separator for an electricity storage device according to the present disclosure can be suitably used as a separator for an electricity storage device, such as a lithium ion secondary battery. [Explanation of symbols]
[0129] 1: Polymer matrix 2: Linked domain (bold line) 3: Fibril (thin wire) 4: Hole
Claims
1. A separator for an electricity storage device, comprising a microporous layer (A) as a separator substrate, the microporous layer (A) containing a polyolefin as a main component and a thermoplastic elastomer, The microporous layer (A) contains polypropylene and polyethylene as the polyolefin, The microporous layer (A) contains, based on the total mass of the microporous layer (A), 80.0% by mass or more and 99.5% by mass or less of the polyolefin and 0.5% by mass or more and 20.0% by mass or less of the thermoplastic elastomer, and contains, based on the total mass of the polyolefin excluding the thermoplastic elastomer, 80.0% by mass or more and 99.5% by mass or less of the polypropylene and 0.5% by mass or more and 20.0% by mass or less of the polyethylene; The microporous layer (A) has a melt flow rate (MFR) of 0.90 g / 10 min or less when measured under a load of 2.16 kg at a temperature of 230° C.
2. The melt tension Mt of the microporous layer (A) at 240°C A The separator for an electricity storage device according to claim 1 , wherein the compressive strength is 10 mN or more and 35 mN or less.
3. The separator for an electricity storage device according to claim 1 or 2, wherein the microporous layer (A) has a weight average molecular weight (Mw) of 250,000 or more and 1,500,000 or less.
4. 4. The separator for an electricity storage device according to claim 3, wherein the microporous layer (A) has a molecular weight distribution (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn), of 3 or more and 30 or less.
5. The microporous layer (A) has an endothermic peak A having a peak value in the range of 100° C. or more and 145° C. or less and an endothermic peak B having a peak value in the range of 155° C. or more and 175° C. or less in a differential scanning calorimetry (DSC) curve during a temperature rise process, and the area S of the endothermic peak A is A and the area S of the endothermic peak B B Ratio S B / S A The separator for use in an electricity storage device according to claim 1 or 2, wherein m is 2 or more and 200 or less.
6. 3. The separator for an electricity storage device according to claim 1, wherein the microporous layer (A) has a melt flow rate (MFR) of 0.30 g / 10 min or more when measured under a load of 2.16 kg at a temperature of 230°C.
7. 3. The separator for an electricity storage device according to claim 1 or 2, wherein the microporous layer (A) contains 90.0% by mass or more of the polyolefin and 10.0% by mass or less of the thermoplastic elastomer based on the total mass of the microporous layer (A), and contains 90.0% by mass or more of the polypropylene and 10.0% by mass or less of the polyethylene based on the total mass of the polyolefin excluding the thermoplastic elastomer.
8. The separator for an electricity storage device according to claim 1 or 2, wherein the polypropylene has a weight average molecular weight (Mw) of 300,000 or more and 1,300,000 or less.
9. 13 3. The separator for an electric storage device according to claim 1, wherein the polypropylene has a pentad fraction of 94.0% or more as measured by C-NMR (nuclear magnetic resonance).
10. 3. The electricity storage device separator according to claim 1, wherein the polyethylene has a weight average molecular weight (Mw) of 100,000 or more and 1,800,000 or less.
11. 3. The power storage device separator according to claim 1, wherein the thermoplastic elastomer contains, as a repeating unit, at least one selected from the group consisting of ethylene, propylene, and 1-butene.
12. 3. The power storage device separator according to claim 1, wherein the separator substrate is a single layer of the microporous layer (A) or a multilayer containing the microporous layer (A), and the porosity of the separator substrate is 40% or more and 60% or less.
13. The separator for an electricity storage device according to claim 1 or 2, wherein the separator substrate has a thickness of 3 μm or more and 20 μm or less.
14. 3. The separator for an electricity storage device according to claim 1, wherein the area average long pore diameter calculated by analysis of a scanning electron microscope (SEM) image of an MD-ND cross section of the microporous layer (A) is 50 nm or more and 500 nm or less.
15. 3 . The separator for an electricity storage device according to claim 1 , wherein the separator substrate has a TD heat shrinkage rate of 5% or less at a temperature of 105° C. for 1 hour.
16. The separator for an electricity storage device according to claim 1 or 2, wherein the separator substrate has an MD heat shrinkage rate of 20% or less at a temperature of 105° C. for 1 hour.
17. The separator for an electricity storage device according to claim 1 or 2, wherein the separator substrate has an MD tensile elongation of 20% or more and 60% or less.
18. The separator substrate has a melt tension Mt A The melt tension Mt B The separator for an electricity storage device according to claim 1 or 2, comprising a microporous layer (B) which is
19. An electricity storage device comprising: a positive electrode; a negative electrode; and the electricity storage device separator according to claim 1 or 2 disposed between the positive electrode and the negative electrode.
20. The power storage device according to claim 19 , wherein the positive electrode contains lithium iron phosphate as a positive electrode active material.
21. The following steps: An annealing step of annealing a resin sheet containing polypropylene, polyethylene, and a thermoplastic elastomer at a temperature of 135° C. or more and 160° C. or less; and A heat treatment step of stretching the annealed resin sheet in the MD at a temperature of 130° C. or more and 155° C. or less; The method for producing the separator for an electricity storage device according to claim 1 or 2, comprising:
Citation Information
Patent Citations
Porous film, separator for lithium battery using the same, and battery
JP2010111832A
Improved microlayer membranes, improved battery separators, and related methods
WO2018089748A1
Separator for electric storage device
WO2019103947A2
Separator for power storage device
WO2020196120A1